siRNA-Finder (si-Fi) Software for RNAi-Target Design and Off-Target Prediction - Lück, Stefanie; Kreszies, Tino; Strickert, Marc; Schweizer, Patrick; Kuhlmann, Markus; Douchkov, Dimitar (Frontiers in Plant Science, 2019)
RNA interference (RNAi) is a technique used for transgene mediated gene silencing based on the mechanism of post-transcriptional gene-silencing (PTGS). PTGS is a ubiquitous basic biological phenomenon involved in the regulation of transcript abundance and plants´ immune response to viruses. PTGS also mediates genomic stability by silencing of retroelements. RNAi has become an important research tool for studying gene function by strong and selective suppression of target genes. Here we present si-Fi, a software tool for design optimization of RNAi constructs necessary for specific target gene knock-down. It offers efficiency prediction of RNAi sequences and off-targets search, required for the practical application of RNAi. si-Fi is an open source (CC BY-SA license) desktop software that works in Microsoft Windows environment and can use custom sequence databases in standard FASTA format.